A Mixed Joint Universality Theorem for Zeta-Functions. II - Pocevičienė, Vaida; Šiaučiūnas, Darius (Mathematical Modelling and Analysis, 2014)
In the paper, a joint universality theorem on the approximation of analytic functions for zeta-function of a normalized Hecke eigen cusp form and a collection of periodic Hurwitz zeta-functions with algebraically independent parameters is obtained.